L’Inde dans la mise en scène des chefs-d’oeuvre européens d’Ariane Mnouchkine - Hasiuk, Magdalena (Collectanea Philologica, 2016)
The text discusses influences and oriental inspirations, mainly Indian and Japanese, present in the staging of Shakespeare’s plays (Richard II, Henry IV, Part I and Twelfth Night), Euripides (Iphigenia at Aulis) i Aeschylus (Oresteia) in the Théâtre du Soleil. Owing to the incorporation of ‘the imagined orient’ in the Shakespearean cycle, Mnouchkine evoked the image of the world immersed in the supernatural. Placing Iphigenia at Aulis before Oresteia, the director created her own tetralogy. Consciously applying staging strategies, she did not use Greek documents but instead combined documentation from Turkey and the Caucasus with oriental traditions such as kathakali and bharata-natyam. Drawing on references which were unknown (or long since forgotten) and never before used, she staged ‘probably the richest and the most satisfactory of all productions of Athenian tragedies’ (Ubersfeld).